Revision of Errhomeninae and Aphrodinae (Hemiptera, Cicadomorpha) in Italy with remarks on their variability and distribution in adjacent regions and description of three new taxa - Guglielmino, Adalgisa; Bückle, Christoph (Zootaxa, 2015)
A revision of the subfamilies Errhomeninae and Aphrodinae in Italy is presented. Two new species, Anoscopus gorloppus and Anoscopus carlebippus, and one new subspecies Anoscopus albifrons mappus are described. Anoscopus dubius Gębicki & Bednarzyk is established as subspecies of Anoscopus flavostriatus (Donovan) (stat. nov.), Aphrodes siracusae (Matsumura) is transferred to the genus Anoscopus (comb. nov.). Anoscopus samuricus Tshmir is recorded in Italy for the first time. Information concerning ecology and regional distribution is given for all taxa present in Italy. Genital morphology and variability of colouration are figured for many taxa. A morphometric analysis based on measurements of aedeagus and body is conducted for the taxa of the Aphrodes bicincta group. Keys for the Italian species of Aphrodes and Anoscopus are given. Distribution and specific characters of Anoscopus assimilis (Signoret) and Anoscopus alpinus (Wagner) are presented. Differences between Italian populations and conspecific ones in other European regions, and reasons for the particularly high variability in the Alpine areas of Italy are discussed. A list of 19 species and two subspecies, presently recorded from Italy is given.